2019
DOI: 10.1111/dom.13841
|View full text |Cite
|
Sign up to set email alerts
|

Durability of glycaemic control with dapagliflozin, an SGLT2 inhibitor, compared with saxagliptin, a DPP4 inhibitor, in patients with inadequately controlled type 2 diabetes

Abstract: Dapagliflozin is associated with greater reductions in HbA1c and weight than saxagliptin in management of type 2 diabetes mellitus (T2DM). The present post hoc analyses compared the durability of these effects over short‐ and long‐term follow‐up in patients with T2DM who were inadequately controlled with metformin (≥1500 mg/day) and who were receiving either dapagliflozin (10 mg/day) or saxagliptin (5 mg/day). Failure of glycaemiccontrol was assessed using the slope of the change in HbA1c from baseline‐over‐ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…A previous summary of clinical trials pointed out that SGLT2 inhibitors appear to show a relatively longer duration of effect on glycemic control (in terms of time to return of HbA1c to baseline at a maximum dose of single oral agent) than other oral antidiabetic drugs, including metformin, SU and DPP-4 inhibitors [45]. Similarly, a recent post hoc analysis suggested a greater durability of glycemic control with the SGLT2 inhibitor dapagliflozin, in patients with T2DM who were inadequately controlled with metformin, compared to that with the DPP-4 inhibitor saxagliptin [46].…”
Section: Discussionmentioning
confidence: 99%
“…A previous summary of clinical trials pointed out that SGLT2 inhibitors appear to show a relatively longer duration of effect on glycemic control (in terms of time to return of HbA1c to baseline at a maximum dose of single oral agent) than other oral antidiabetic drugs, including metformin, SU and DPP-4 inhibitors [45]. Similarly, a recent post hoc analysis suggested a greater durability of glycemic control with the SGLT2 inhibitor dapagliflozin, in patients with T2DM who were inadequately controlled with metformin, compared to that with the DPP-4 inhibitor saxagliptin [46].…”
Section: Discussionmentioning
confidence: 99%
“…CoF can be used as a surrogate marker to quantify the decline in beta‐cell function. We observed lower CoF in the treatment groups of patients who did not experience weight gain 7,8,10,18,29 . Losing weight has been reported to benefit beta‐cell function 11,46,47 through a mechanism that is not completely understood 48–51 .…”
Section: Discussionmentioning
confidence: 65%
“…received insulin therapy. Furthermore, eight studies reported outcomes for the treatment failure rate, [7][8][9] the rescue medication rate, [17][18][19][20] or the treatment intensification rate 10 (Table S3). We also analysed seven randomized controlled trials reporting the long-term effect of weight management on glycaemic durability to compare the long-term therapeutic efficacy of different degrees of weight loss.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently study found that the durability of glycemia control with dapagliflozin was greater than saxagliptin in patients with T2DM, which lasted more than 24 weeks. [ 29 ] Other study indicated that dapagliflozin plus saxagliptin as add-on to metformin also exhibit better tolerance in glycemia control. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%